Taxonomy and distribution of the Afrotropical genus Anchophthalmops Koch, 1956 with a key to species (Coleoptera: Tenebrionidae: Pedinini) - Kamiński, Marcin Jan (Zootaxa, 2013)
The taxonomic and distributional data concerning the representatives of the genus Anchophthalmops were revised. Lectotypes for Anchophthalmops foveipennis and A. ventralis were designated to fix the taxonomic status of these species. A. neumanni and A. zablockii were described as new species. Maximum entropy modeling was used to test the probability of occurrence of A. menouxi on Madagascar. An identification key is provided to all known species of Anchophthalmops.